Effects of Avocado Consumption on Gastrointestinal Microbial Metabolite Concentrations and Taxa Abundances: A Randomized, Controlled Trial (OR23-07-19). (13th June 2019) - Thompson, Sharon; Edwards, Caitlyn; Reeser, Ginger; Khan, Naiman; Holscher, Hannah
Abstract: Objectives: Avocados are rich in dietary fiber and monounsaturated fatty acids, nutrients that have been independently connected with metabolic health benefits and changes to the gastrointestinal (GI) microbiota. However, little is known regarding the impact of avocado consumption on GI microbial community composition and microbially-derived metabolites, particularly among adults with overweight or obesity. Methods: Adults ( n = 160) between 25–45 years of age with BMI ≥ 25.0 kg/m 2 were enrolled in an investigator-blinded, parallel arm, randomized, controlled trial. Participants consumed isocaloric meals with or without fresh Hass avocado once daily for 12-weeks. Compliance was evaluated with daily self-report records. Fecal microbially-derived metabolites, including acetate, propionate, butyrate, isovalerate, valerate, and isobutyrate were quantified using gas chromatography mass spectroscopy on a dry matter basis. Following fecal DNA extraction, microbial analyses were conducted by sequencing the V4 region of the 16S rRNA gene. Sequence data were analyzed using DADA2 and QIIME version 2. Per protocol (PP; > 80% meal consumption) and intent-to-treat (ITT) approaches were applied and generalized linear mixed models were assessed for treatment, time, and treatment by time interactions in SAS version 9.4. Results: The intervention was completed by 88% ( n = 140) of participants, average meal compliance among both groups was 90%, and 83% ( n = 132) of participants met PP criteria. Microbiota analyses were completed for 156 ITT and 109 PP participants, respectively. ITT time by treatment analyses indicated that compared to control, avocado consumption increased acetate ( P < 0.01) and total short-chain fatty acid (SCFA; P = 0.02) concentrations and increased the relative abundances of Faecalibacterium ( P = 0.01). PP time by treatment analyses revealed that avocado consumption increased acetate concentrations ( P < 0.01), increased the relative abundances of Lachnospira ( P = 0.04), and trended to increase Faecalibacterium ( P = 0.08). Conclusions: Fresh Hass avocado intake increased the relative abundances of microbes capable of fiber fermentation and SCFA production among adults with overweight or obesity, providing valuable evidence for the impact of this nutrient dense food on the GI microbiota. Funding Sources: Support for this research was provided by the Hass Avocado Board and the USDA National Institute of Food and Agriculture, Hatch project 1009249.